1992
DOI: 10.1017/s0022112092002143
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady shock propagation in a steady flow nozzle expansion

Abstract: The flow field produced when a strong shock wave propagates into a steady flow expansion has been investigated numerically, experimentally and analytically. The experiments were conducted with a shock tube which was modified to allow steady flow to be established in a hypersonic nozzle prior to arrival of the shock. It has been found that the axial density distribution associated with the prior steady flow allows the unsteady flow following the nozzle primary starting shock to accelerate from supersonic to hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This scenario mimics on a small scale unsteady behaviours observed in shock tubes, for instance the unsteady shock propagation observed by Stalker and Mudford, in a steady flow nozzle expansion. [25] These authors observed that the axial density distribution associated with the prior steady flow allows the unsteady flow following the nozzle primary starting shock to accelerate from supersonic to hypersonic speeds.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario mimics on a small scale unsteady behaviours observed in shock tubes, for instance the unsteady shock propagation observed by Stalker and Mudford, in a steady flow nozzle expansion. [25] These authors observed that the axial density distribution associated with the prior steady flow allows the unsteady flow following the nozzle primary starting shock to accelerate from supersonic to hypersonic speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 15(c) displays a time resolved spectrum of the radiation from the shock layer in the stagnation region of a hemisphere at an inertia of any practical diaphragm is too large for it to be removed from the test flow in the few tens of microseconds of test time available in a high performance shock tube. The diaphragm can be rendered unnecessary by arranging that, immediately prior to a test, a steady flow of test gas is established in the nozzle (56,57) . This allows the nozzle starting process to be completed as rapidly as with a pre-evacuated nozzle and a massless diaphragm.…”
Section: Dissociating Hypervelocity Flowsmentioning
confidence: 99%